ภาพสะท้อนปัญหาสงครามในวรรณกรรมเยาวชนเรื่องเมื่อวานนี้ ของศรี เกศมณี: Reflection of War Problems in Young Adult Literature Mueawannee by Sri Kesamanee - กระโด ฮัซวานี; ดือมาลี ฮาซันสนิ; จีนนุ่น พัชลินจ์; ชูแก้ว ปริยากรณ์ (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
This descriptive and analytical research article aims to study the reflections on war problems and the literary techniques used to present them in the young adult literature Mueawannee by Sri Kesamanee. The findings reveal that the primary cause of the war was Field Marshal Plaek Phibunsongkhram’s decision to ally with Japan. This decision led to consequences across six dimensions: 1) Political and administrative, 2) Economic, 3) Social, 4) Educational, 5) Cultural, and 6) Psychological impacts. Furthermore, the author reflects these war problems through four distinct literary techniques: 1) A flashback plot structure; 2) Characters who experience the hardships of war, impacting their thoughts, emotions, and feelings; 3) Combat scenes that convey the fear and chaos of warfare; and 4) A narrative perspective delivered through a first-hand experienced narrator. Ultimately, the author portrays these war conflicts to raise awareness among the youth regarding the brutality of war at the national, societal, and individual levels.